2013
DOI: 10.6001/ekologija.v58i3.2532
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of invasive muskrats (Ondatra zibethicus) and impact on ecosystem

Abstract: The muskrat (Ondatra zibethicus L.) after being introduced to Europe quickly colonized new areas. They occupied Northern, Eastern and Central Europe. One of the reasons for their successful invasion into new areas was the release of animals in numerous places and their subsequent successful self-spreading from these places. However, this semi-aquatic rodent negatively impacts the ecosystem (causes damages of watercourse embankment through burrowing, consumes crops). The species possesses a high potential for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…The impacts from potential mechanisms of predation were the direct consumption of adult unionid mussels by fish, direct competition with or predation on indigenous fish hosts, and the unintentional consumption or disturbance of juvenile mussels through bioturbation of bottom sediments (Fei et al, ; Poos et al, ). Mortality as a result of predation occurred after failed consumption, via desiccation following transfer to the terrestrial environment (Skyrienė & Paulauskas, ), as has been observed along some New Zealand streams (Moore, pers. observ.).…”
Section: Discussionmentioning
confidence: 85%
“…The impacts from potential mechanisms of predation were the direct consumption of adult unionid mussels by fish, direct competition with or predation on indigenous fish hosts, and the unintentional consumption or disturbance of juvenile mussels through bioturbation of bottom sediments (Fei et al, ; Poos et al, ). Mortality as a result of predation occurred after failed consumption, via desiccation following transfer to the terrestrial environment (Skyrienė & Paulauskas, ), as has been observed along some New Zealand streams (Moore, pers. observ.).…”
Section: Discussionmentioning
confidence: 85%
“…The muskrat is absent in the Mediterranean, and grazing pressure may be lower in Scandinavia due to more severe winters and higher predation (Atsimo, ). In Central Europe the muskrat, although widespread (Skyriene & Paulauskas, ), has not frequently been reported as a cause of reed decline (Ostendorp, ; Ostendorp, ; Rücker et al ., ; Dienst et al ., ). It might have been overlooked there as well.…”
Section: Discussionmentioning
confidence: 99%
“…The history and result of muskrat introductions in Europe, as well as their dispersal rates and the impact of muskrat on biota and their habitats in north‐western Europe, are discussed in Danell . Nowadays, muskrats are present everywhere in the lowlands of north‐western Europe, and in some regions a control programme is in place. With how much conviction and by what strategy the control is implemented, however, vary greatly by region.…”
Section: Introductionmentioning
confidence: 99%